Integrasi Sistem Perizinan Berusaha Berbasis Risiko dan Sertifikasi Halal untuk Mewujudkan Layanan Terpadu yang Efisien bagi Pelaku Usaha - Titie Rachmiati Poetri; , Eko Prasetyo (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
Current business licensing governance in Indonesia exhibits an integration between the risk-based OSS-RBA System and halal certification. While OSS-RBA determines licensing based on business risk levels, halal certification emphasizes religious compliance, yet these frameworks operate in parallel without integration. A critical research gap exists because OSS-RBA does not incorporate ethical, moral, and spiritual risk factors core elements of halal certification. This study aims to analyze the urgency of integrating halal certification into OSS-RBA and formulate an ideal integration model. Using normative legal methods with statutory and conceptual approaches, data were collected through library research examining primary legal documents including Government Regulation Number 28 of 2025, Number 42 of 2024, the Halal Product Guarantee Law, and secondary literature on Maqashid Shariah. The study finds that the concept of halalan thayyiban has expanded through a progressive Maqashid Shariah paradigm, now encompassing environmental preservation and waste management obligations. The proposed integration model consists of an electronically integrated service system governed by